Structural and electronic properties of ZnO: A first-principles density-functional theory study within LDA(GGA) and LDA(GGA)+U methods - Jafarova, V.N.; Orudzhev, G.S. (Solid state communications, 2021)
In this article, the structural and electronic properties of bulk ZnO have been studied using the plane-wave-based pseudopotential density functional theory (DFT). The structural parameters, band structure (BS), and density of states (DOS) of ZnO wurtzite structure have been investigated by Quantum Wise within LDA (GGA) and LDA (GGA)+U methods by Fritz-Haber-Institute (FHI) pseudopotentials. The calculated band gaps using Hubbard U semiempirical corrections are in agreement with previous experimental works and shows both the valence band maximum and conduction band minimum located at the Γ point of the Brillouin zone (BZ).